Development of the Ward Nurses' Perspective-taking of the Staff Receiving Discharged Patients Scale: An observational study of ward nurses. - Shingo Tanaka; Masatoshi Saiki; Yukie Takemura (PLoS ONE)
Introduction Discharge planning involves coordinating between different care settings. Failed coordination can lead to delayed care at the facilities receiving discharged patients. Nurses who implement discharge planning must consider the circumstances of the staff receiving the discharged patients. Objective This study aims to develop a nurses' perspective-taking scale for measuring the cognitive process of imagining a staff's situation when receiving discharged patients. Methods An online survey was conducted from September to November 2021 with nurses in Japanese acute care hospitals, using a 20-item questionnaire based on interviews and a literature review. Item reduction was conducted based on inter-item correlations, item-total correlations, and exploratory factor analysis. Confirmatory factor analysis was performed. For the exploratory and confirmatory factor analysis, the samples were randomly split in half and tested. Cronbach's alpha, intraclass correlation coefficients, and correlation coefficients were calculated using both self-developed and pre-existing measures. Results The questionnaire was distributed to 1,289 individuals, and 416 valid responses were obtained. Item reduction and exploratory factor analysis resulted in a 10-item scale with two subscales, "imagine-other" (six items), which is imagining the other person's situation, and "imagine-self" (four items), which is imagining oneself in the other person's situation. The goodness-of-fit indices were as follows: comparative fit index, 0.95; root mean square error of approximation, 0.08; and standardized root mean squared residual, 0.06. Correlation coefficients with existing scales were 0.38, 0.57, and -0.33. Cronbach's alpha was 0.89, and the intraclass correlation coefficient was 0.54. Conclusion The newly developed scale proved to be reliable, valid, and suitable for use. This scale can measure the degree of perspective-taking by nurses, which can improve collaboration between facilities and the effectiveness of discharge planning.